Systematic Literature Review: Metode Bar Model Dalam Pembelajaran Matematika - Desmia, Seli; Lidinillah, Dindin Abdul Muiz; Apriani, Ika Fitri (Peneliti.net, 2024)
The Bar Model method in learning can be used to make it easier for teachers to convey learning messages, increase the activity and creativity of students in the learning process so that it can finally improve students' problem-solving abilities. This study aims to conduct a literature review related to the effectiveness of the Bar Model method in learning mathematics in elementary school mathematics. The research method chosen in this study is the SLR (Systematic Literature Review) method. Data collection was carried out by documenting all articles that have similar research in this research report. The articles used in this study were 10 accredited national journal articles at sinta 1 to sinta 4 obtained from various sources. Based on this research, it was found that the Bar Model method in learning mathematics can improve students' problem solving abilities. Based on a literature review conducted by the Bar Model method, it can be developed in learning mathematics in elementary school mathematics.